Detailed Study on the Interfacial Interaction between Different Polyoxometalates and Tetronic Block Copolymers Exploring the Langmuir-Blodgett Technique - Roy, Dipali (Langmuir : the ACS journal of surfaces and colloids, 2024)
Polyoxometalates (POMs) interact with various biologically relevant entities. A basic understanding of this interaction is very important for various applications in the biological field. In this work, the focus is on the study of the interaction between tetronics and Keggin POMs. T701 and T90R4 are the two tetronics considered here; they have different solubilities in water due to different PPO/PEO ratios. The arrangement of PPO and PEO is also different with respect to the central ethylenediamine groups. Three different Keggin-type POMs, phosphomolybdic acid (PMA), phosphotungstic acid (PTA), and silicotungstic acid (STA), with different charge densities are chosen for an elaborate investigation using Langmuir-Blodgett technique. The observation is analyzed thoroughly, which shows both electrostatic interaction and adsorption of POMs on the PPO blocks of the tetronics due to the chaotropic effect, which is responsible for the binding of POMs (in subphase) with the tetronic monolayer. This interaction results in an expanded yet rigid monolayer for POM-tetronic association on the surface. Surface pressure vs mean molecular area isotherm is the key characterization to reach the conclusion. UV-vis spectroscopy, NMR, ITC, ellipsometric studies, FTIR, and SEM also serve as supportive characterization techniques